Flow simulation considering adsorption boundary layer based on digital rock and finite element method - Yang, Yong-Fei; Wang, Ke; Lv, Qian-Fei; Askari, Roohollah; Mei, Qing-Yan; Yao, Jun; Hou, Jie-Xin; Zhang, Kai; Li, Ai-Fen; Wang, Chen-Chen (Petroleum science, 2021)
Due to the low permeability of tight reservoirs, throats play a significant role in controlling fluid flow. Although many studies have been conducted to investigate fluid flow in throats in the microscale domain, comparatively fewer works have been devoted to study the effect of adsorption boundary layer (ABL) in throats based on the digital rock method. By considering an ABL, we investigate its effects on fluid flow. We build digital rock model based on computed tomography technology. Then, microscopic pore structures are extracted with watershed segmentation and pore geometries are meshed through Delaunay triangulation approach. Finally, using the meshed digital simulation model and finite element method, we investigate the effects of viscosity and thickness of ABL on microscale flow. Our results demonstrate that viscosity and thickness of ABL are major factors that significantly hinder fluid flow in throats.